Highly selective electroreductive linear dimerization of electron-deficient vinylarenes. (3rd December 2021) - Ning, Shulin; Zheng, Lianyou; Bai, Ya; Wang, Shutao; Wang, Siyu; Shi, Lingling; Gao, Qiansong; Che, Xin; Zhang, Zhuoqi; Xiang, Jinbao
Abstract: A direct electroreductive dimerization of electron-deficient vinylarenes for the synthesis of 1, 4-diarylbutane has been developed using a simple undivided cell with inexpensive carbon electrodes at room temperature. The control and deuterium-labeling experiments of electroreductive dimerization suggest that the hydrogen source comes from the solvent CH3 CN. This protocol provides a mild and efficient route for the construction of C–C bond in moderate to good yields with high regioselectivity and broad substrate scope. Graphical abstract: A highly regioselective linear dimerization of electron-deficient vinylarenes under mild electrochemical conditions is introduced, which could provide direct access to a diverse set of 1, 4-diarylbutanes. Image 1